Environmental impact resource management in rural tourism: a post-positivism perspective - Chia, Kei Wei; Sehkaren, Vikneswaran Nair; Ramachandran, Sridar; Shuib, Ahmad (2011)
Malaysia has rich natural tourism resources that are readily available to be explored. The environment quality is vital for tourism; particularly for nature-based destination in rural setting. The rapid tourism development has caused the gradual destruction of environmental resources on which it depends on. Therefore, the negative environmental impacts can be reduced if rural tourism is managed in a responsible manner. In order to ameliorate the negative environmental impacts, the quality of tourism resources must be well maintained and managed. This paper attempts to identify problems that are contributing to rural tourism. This paper will first provide discussion on the potential environmental impacts caused by rural tourism. It will then discuss the major paradigms followed by the post-positivism as the philosophical position of this research.